Forced Lockdown And Measures Taken By The Government Of India And The Various State Governments Under Existing Legal Framework. Does It Violates The Rights Under Other Laws? (Journal of Namibian Studies : History Politics Culture, 2023)
The Government of India has imposed an unprecedented 21-day national lockdown, as part of a series of steps to reduce the transmission of the Covid-19, on 25.03.2020. The virus had assumed the status of a pandemic, impacting almost every country across the globe including India. The measures taken by the government of India and various other state governments poses serious legal challenges.